Effect of substituents on 3(S)-amino-1-hydroxy-3,4-dihydroquinolin-2(1H)-one: a DFT study - Lira J. (2019)
PF04859989 is a potential novel drug designed to attenuate symptoms of Schizophrenia. We analyzed the substitution effect on PF04859989 using three functional, which included the long-range correction. The substituents were both donor and attractor electrons, in two positions of the fused-ring molecule, in positions six and seven. Global reactivity indices were analyzed, finding that it does not present more information except electrophilicity, when analyzed with respect to the Hammet parameter, representing a quadratic correlation closer to the unit. The hydrophobic capacity (cLogP) was considered, finding that the groups such as CH3, CN, Cl and COCH3 increase hydrophobic capacity both in substitution in position six and seven. Additionally, we found that isomers conformations in position three of the amino group marked that equatorial isomers are more stable than the axial ones.